Does Systemic Chemotherapy Influence Skeletal Growth of Young Osteosarcoma Patients as a Treatment-Related Late Adverse Effect? - Manabu Hoshi; Naoto Oebisu; Tadashi Iwai; Yoshitaka Ban; Hiroaki Nakamura (Current Oncology, 2022)
The aim of this study was to investigate the influence of systemic chemotherapy on the skeletal growth of young osteosarcoma patients as a treatment-related late adverse effect. We reviewed the height data of 20 osteosarcoma patients (13 males and 7 females) aged ≤18 years. The average (±SD) age at diagnosis was 14.5 (±3.3) years. The average follow-up interval was 89.6 months. After wide resection of the affected bones, reconstruction with tumor prostheses and auto-bone grafting was carried out in 11 and 9 cases, respectively. Pearson’s correlation coefficient was calculated to evaluate the association between actual and predicted (using Paley’s multiplier method) heights. Z-scores were used to compare the initial and final heights with the Japanese national growth curve. Actual and predicted heights were correlated according to Pearson’s correlation coefficient (R = 0.503). Z-analysis showed that statistical significance (p = 0.04) was noted for the height data Z-scores of patients between ≤10 years and >10 years at the final follow-up. Systemic chemotherapy did not reduce skeletal growth in young osteosarcoma patients as a late adverse effect based on two different evaluation methods. However, patients aged ≤10 years at diagnosis may develop a short stature after systemic chemotherapy.